ChatGPT & Co: AI Transforming Terminological Preparation in Interpreting - Havelka, Ivana (Corpora in Language Learning, Translation and Research: Proceedings of the International Conference Corpora in Language Learning, Translation and Research held at the University of Zadar (August 23–24, 2023), 2025)
Interpreting, as an interdisciplinary field, inherently requires specialized terminology due to its transdisciplinary applications (Lušicky 2019). Terminological preparation is thus a prerequisite for each interpreting assignment. With the advent of new AI tools, this process is undergoing a transformative shift. ChatGPT and similar tools are already used in academia (e.g., Halaweh 2023; Passmore and Tee 2023) but might become more prevalent in terminological preparation (Hsu 2023). This case study delves into the implementation and benefits of chatbots in terminological preparation. Beyond merely providing terminology lists, ChatGPT and Co support the process by facilitating an interactive dialogue that aids in research. This approach not only streamlines terminology extraction but also fosters a deeper understanding and tailored adaptation to specific project needs. The findings of this study show that AI-powered solutions hold the potential to significantly enhance terminological preparation, paving the way for future innovations in the field.